Wetzlar, 2. April '87 - Johannes Rau, Willi Görlach - Hessen wählt hessisch - SPD - Sozialdemokratische Partei Deutschlands (SPD), Landesverband Hessen, Wiesbaden; Kiehne, Wolfgang; Union-Druckerei, Frankfurt am Main
Bemerkungen: stark gerollt